(untitled) (The Conference Hub, 2025)
This article examines modern approaches and ways to develop an entrepreneurial culture in students at higher education institutions. It explores the importance of entrepreneurial thinking as a crucial factor in professional self-realization in a market economy. Pedagogical conditions, methods, and forms of teaching that promote initiative, responsibility, and innovation in students are identified.